Macroanatomical investigations on the dural sinuses in holstein bovine and their extracranial connections - Hakan Yalçın; Kamil Beşoluk; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
In this study, the dural sinus extracranial connections, were investigated in Holstein cows. For this purpose, eight Holstein cows were used as a material. Blue latex were injected through the external juguler vein. It was determined that the dural sinus consisted of the ventral and dorsal systems. The dorsal system is composed of the transversal sinus, temporal sinus, sigmoid sinus, confluens sinuum, dorsal sagittal sinus and straight sinus. The ventral system of the dural sinus is consisted of the ventral petrosus sinus, basilar sinus and cavernosus sinus. It was observed that extracranial connection of vertebra! vein and occipital vein is to be provided by occipılai emissarial vein. It was determined that extracraniaf connection of basilar sinus and ventral petrosal sinus is to be provided hypoglossal n. canal emissarial vein. It was determined that extracranial connection of ventral petrosal sinus and occipital vein is to be provided by jugular foram i rial emissarial vein. It was determined that extracranial connectioned of temporal sinus and pterygoideal plexus is to be provided by retroarticuiar foramina! emissarial vein, it was observed that extracranial vein connection of cavernosal sinus and pterygoideal plexus is to be provided by oval foraminal emissarial vein.lt was determined that extracranial connection of cavernosal sinus and ophthalmic plexus is to be provided by or-bitorotundi foraminal emissarial vein.